Structure and function of the global ocean microbiome - Sunagawa, Shinichi; Coelho, Luis Pedro; Kultima, Jens Roat; Djahanschiri, Bardya; Zeller, Georg F.; Mende, Daniel Richard; Costea, Paul Igor; Hildebrand, Falk; Kandels-Lewis, Stefanie; Bork, Peer (Science, 2015)
Microbes are dominant drivers of biogeochemical processes, yet drawing a global picture of functional diversity, microbial community structure, and their ecological determinants remains a grand challenge. We analyzed 7.2 terabases of metagenomic data from 243 Tara Oceans samples from 68 locations in epipelagic and mesopelagic waters across the globe to generate an ocean microbial reference gene catalog with >40 million nonredundant, mostly novel sequences from viruses, prokaryotes, and picoeukaryotes. Using 139 prokaryote-enriched samples, containing >35,000 species, we show vertical stratification with epipelagic community composition mostly driven by temperature rather than other environmental factors or geography. We identify ocean microbial core functionality and reveal that >73% of its abundance is shared with the human gut microbiome despite the physicochemical differences between these two ecosystems.
Gesehen am 23.06.2020